2017
DOI: 10.1097/tp.0000000000001160
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for Recurrence of Primary Focal Segmental Glomerulosclerosis After Kidney Transplantation: Clinical Outcomes

Abstract: In kidney transplantation recipients with recurrent FSGS, rituximab therapy may be a recommended treatment for cases that have failed either the initial treatment or weaning from PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…Randomized controlled trials are lacking, and disease definitions, treatment regimens, and definitions of response to therapy vary greatly. Therapeutic strategies consist of methylprednisolone, high‐dose cyclosporine, cyclophosphamide, PF, plasma filtration, IA, LDL‐apheresis, IVIG, R, and ofatumumab . In this study, we investigated local preventive and/or therapeutic policies of recurrent FSGS after renal transplantation through a survey sent to all members of the ESPN.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled trials are lacking, and disease definitions, treatment regimens, and definitions of response to therapy vary greatly. Therapeutic strategies consist of methylprednisolone, high‐dose cyclosporine, cyclophosphamide, PF, plasma filtration, IA, LDL‐apheresis, IVIG, R, and ofatumumab . In this study, we investigated local preventive and/or therapeutic policies of recurrent FSGS after renal transplantation through a survey sent to all members of the ESPN.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its efficacy in some cases supports the hypothesis that B lymphocytes are involved in certain forms of FSGS through the production of some antibodies [16]. A recent study has described that its administration appears to be particularly useful for patients in whom conventional treatment with plasma exchange, steroids and calcineurin inhibitors has failed because it obtains a 50% remission rate in these cases [17]. …”
Section: Discussionmentioning
confidence: 75%
“…The dosage of Rituximab in previous studies was between 1 and 4 doses [17, 18]. In our case, the aggressive recurrence along with the patient’s tolerance of the treatment, led us to administer 5 doses, although 3 or 4 doses may have been enough.…”
Section: Discussionmentioning
confidence: 98%
“…Ponticelli reported that partial or complete remission was achievable using PE or IA in 63% of adult patients [148]. Rituximab is also known to be an effective treatment for FSGS and was more effective with PE [156,157]. However, other reports have noted that rituximab showed an intermediate, or no, response [158].…”
Section: Fsgsmentioning
confidence: 99%